Productivity convergence and economic growth: A frontier production function approach - Christopher Mark Cornwell; Jens-Uwe Wächter (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1999)
The empirical growth literature has focused on capital accumulation but largely ignored productivity growth. To address this imbalance, we propose a methodology for analyzing productivity convergence based on frontier production functions. We examine whether departures from the frontier are cointegrated, determine the extent and speed of catch-up, and assess the importance of efficiency changes for economic growth. Using a sample of 26 OECD countries from 1965-90, we find convergence and catch-up is fairly strong among EU countries but not among the G-7. Overall, the ability to absorb new technology is an important source of economic growth.
Keywords: C2; O47; O57; 330; cointegration; convergence; growth; productivity; unit root